2005
DOI: 10.32398/cjhp.v3i1.1749
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Findings in an Alternative High School

Abstract: It has been well documented that today’s adolescents are at great risk for health-compromising behaviors. Researchers have identified values orientation and values education as important change agents in reducing these “risky” behaviors. It has also been suggested that an individual’s values orientation that is focused on the future and in a societal view of life is associated with protective and resilience factors with fewer health-compromising behaviors. This study examined adolescents’ values orientation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…[ 13 ] found only traditional (conformity, tradition, security) and humanitarian (benevolence, universalism/equality) values were associated with lower substance-use. However, a family study of American adolescents (aged 18), found that while traditional values were again protective, humanitarian (humanitarianism and equality) values were associated with higher (general) substance-use [ 14 ]. This last result may be attributable to the over-sampling of 'unconventional families'.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ] found only traditional (conformity, tradition, security) and humanitarian (benevolence, universalism/equality) values were associated with lower substance-use. However, a family study of American adolescents (aged 18), found that while traditional values were again protective, humanitarian (humanitarianism and equality) values were associated with higher (general) substance-use [ 14 ]. This last result may be attributable to the over-sampling of 'unconventional families'.…”
Section: Introductionmentioning
confidence: 99%